1995
DOI: 10.1074/jbc.270.52.31077
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis of Evolutionary Conserved Carboxylic Amino Acids in the Chitosanase from Streptomyces sp. N174 Reveals Two Residues Essential for Catalysis

Abstract: The comparison of four sequences of prokaryotic chitosanases, belonging to the family 46 of glycosyl hydrolases, revealed a conserved N-terminal module of 50 residues, including five invariant carboxylic residues. To verify if some of these residues are important for catalytic activity in the chitosanase from Streptomyces sp. N174, these 5 residues were replaced by site-directed mutagenesis. Substitutions of Glu-22 or Asp-40 with sterically conservative (E22Q, D40N) or functionally conservative (E22D, D40E) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 24 publications
(38 reference statements)
1
56
0
Order By: Relevance
“…5A). Using the homology detection program HHpred (28), we found that the sequence following the PBD domain of VgrG3 shares conserved residues with the catalytic sites of lysozyme-like chitosanases (29)(30)(31). When cloning VgrG3 into the pBADexpression vector, we noticed that induced expression of this protein leads to lysis of E. coli culture.…”
Section: Resultsmentioning
confidence: 99%
“…5A). Using the homology detection program HHpred (28), we found that the sequence following the PBD domain of VgrG3 shares conserved residues with the catalytic sites of lysozyme-like chitosanases (29)(30)(31). When cloning VgrG3 into the pBADexpression vector, we noticed that induced expression of this protein leads to lysis of E. coli culture.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrolytic activity of E22Q was known to be lower than 0.1% of that of the wild type enzyme. 7) We found that the transition temperature (Tm) increased in the presence of (GlcN)n, 9) and that the stabilization effect became larger with the increasing chain length of the added oligosaccharide. 10) Similar experiments with the D57A chitosanase revealed that protein stability is not enhanced upon addition of (GlcN)3.…”
Section: Enzymatic Activities Of Asp57-mutated Chitosanases Toward Chmentioning
confidence: 96%
“…The catalytic residues were found to be Glu22 and Asp40 by site directed mutagenesis. 7) From the distribution of electrostatic potential on the enzyme surface, the entire region of substrate binding cleft was found to be densed with electronegative charges. Thus, we supposed that carboxylic amino acid residues could play an important role in determining the mode of substrate binding of this chitosanase.…”
Section: N174 Chitosanasementioning
confidence: 99%
“…1), were severely affected as to their hydrolyzing activity against completely deacetylated chitin (Table 4), as the E22Q and D37N mutants of the N174 chitosanase. 16) The data suggest that Glu23 and Asp41 act as active centers in the Cto1 protein. …”
Section: Overproduction and Purification Of The Recombinant Cto1 Proteinmentioning
confidence: 97%
“…14) In N174 chitosanase, two acidic amino acid residues, Glu22 and Asp40, the corresponding amino acid residues of which are conserved among family-46 chitosanases, act as active centers, as follows: Glu22 donates the proton to the glycosyl oxygen atom to split the -1,4-glycosidic linkage, and the water molecule activated by the carboxylate of Asp40 then attacks the C1 carbon of the substrate sugar residue to produce an -anomer as the enzymatic product. [15][16][17] y To whom correspondence should be addressed. Present address: Graduate School of Advanced Integration Science, Chiba University, 648 Matsudo, Matsudo, Chiba 271-8510, Japan; Tel: +81-47-308-8870; Fax: +81-47-308-8720; E-mail: andnand@faculty.chiba-u.jp * Present address: Graduate School of Advanced Integration Sciences, Chiba University, 648 Matsudo, Matsudo, Chiba 271-8510, Japan Abbreviations: CBB, Coomassie Brilliant Blue; Cto1, chitosanase 1; N-terminal, amino-terminal; PAGE, polyacrylamide gel electrophoresis; PCR, polymerase chain reaction Here we report the purification and characterization of a novel chitosanase from a chitosan-degrading bacterial strain isolated from soil.…”
mentioning
confidence: 99%